Winter Exponential Smoothing: Sales Forecasting on Purnama Jati Souvenirs Center - Fahrobby Adnan; Putri Damayanti; Gama Fajarianto; Antonius Cahya Prihandoko (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Forecasting is the process of making predictions of the future based on past and present data and most commonly by analysis of trends. In sales area, an accurate sales forecasting system will help the company to improve the customers' satisfaction, reduce destruction of products, increase sales revenue and make production plan efficiently. Purnama Jati is a typical Jember souvenir place like "prol tape", "pia tape", "brownies tape" and so forth. Every day, sales on every outlet is uncertain so Purnama Jati repeatedly send to the outlets if the stock has run out. This research will focuse on "prol tape" cake, "pia tape" cake product as the research object. In this research we will use winter exponential smoothing as a forecasting method due to suitable character with the case.